2015
DOI: 10.1080/09593330.2015.1068379
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wastewater treatment plants' operational conditions on activated sludge microbiological and morphological characteristics

Abstract: The effect of wastewater composition and operating conditions in activated sludge (AS) microbiological and morphological characteristics was studied in three AS wastewater treatment plants (WWTPs): (a) a high organic load slaughterhouse AS WWTP, operating at complete solids retention, monitored from its start-up and for 425 days; (b) a seasonally operational, low nitrogen load fruit canning industry AS WWTP, operating at complete solids retention, monitored from its start-up and until the end of the season (87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
17
1
Order By: Relevance
“…The authors have identified SBI as a very useful indicator for determining both the condition of activated sludge and the analysis of biological working conditions of treatment plants. Identification of micro-fauna in mixed wastewater (domestic and industrial) has been recognized as an important element by many researchers [22,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The authors have identified SBI as a very useful indicator for determining both the condition of activated sludge and the analysis of biological working conditions of treatment plants. Identification of micro-fauna in mixed wastewater (domestic and industrial) has been recognized as an important element by many researchers [22,[33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Relative small deviations in influent measured characteristics were observed due to the use of an influent equalization tank ( Table 1). The mean COD:N:P ratio in influent was 150:9.8:1.8 (sufficient nutrient content), while the BOD20/COD and BODultimate/COD ratios were 0.91 and 0.98 respectively (highly biodegradable) [15,18].…”
Section: Wwtp-1mentioning
confidence: 99%
“…The biomass of WWTP-1 is characterized by (a) the growth of metazoan such as rotifers, especially after reaching stabilization phase, (b) small biomass flocs and (c) good settling characteristics (SVI < 100) [21]. Filamentous species have never been observed in WWTP-1, probably due to the higher than 4 mg/L DO concentration in the aerobic stages and the use of the preliminary stage that acts as a microbial selector [13][14][15].…”
Section: Wwtp-1mentioning
confidence: 99%
See 2 more Smart Citations